8th International symposium on delivery of functionality in complex food systems (DOF 2019). Issue 11 (30th October 2020) - Vicente, António A.; Boland, Mike; Livney, Yoav D.
Abstract : Antonio A. Vicente, Mike Boland & Yoav D. Livney introduce the Food & Function themed collection on the 8 th international symposium on delivery of functionality in complex food systems (DOF 2019).